Community Residents' Beliefs About Neighborhood Corner Stores in 2 Latino Communities: Implications for Interventions to Improve the Food Environment. Issue 3 (3rd July 2017) - Sharif, Mienah Z.; Albert, Stephanie L.; Chan-Golston, Alec M.; Lopez, Gilberto; Kuo, Alice A.; Prelip, Michael L.; Ortega, Alexander N.; Glik, Deborah C.
ABSTRACT: We assessed community residents' perceptions of corner stores to better understand what facilitates and deters patronage at these food outlets. Data came from 978 household interviews in 2 Latino communities undergoing corner store interventions. Chi-square tests, an independent sample t test, and a multivariate logistic regression were conducted to assess the relationship between residents' perceptions about corner stores and their reported patronage at these food outlets. Residents reported that corner stores do not sell a variety of fruits and vegetables and are not places where one can get information about healthy eating. Convenience, cleanliness, positive customer service, availability of culturally appropriate items, and availability of quality fresh fruit increased the odds of store patronage. Simply providing healthy foods will not incentivize patrons to purchase them. Corner store interventions can be more effective if they address the characteristics that community residents prioritize.